2019
DOI: 10.1108/aia-09-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences with an adolescent female and male with Autism Spectrum Disorder (ASD) in India

Abstract: Purpose The purpose of this paper is to compare experiences of two parents of adolescents with Autism Spectrum Disorder (ASD) differing in gender, including their daily routines at school and at home, challenging behaviour, social support and future plans for their children. Design/methodology/approach The parents of the two adolescents with ASD were interviewed with open-ended questions related to their children as well as their personal experiences, along with getting their individual responses for the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…A majority of the studies found that parents and families of children with autism have to go through a lot of difficulties to provide rehabilitation to their children. 17,26,[30][31][32][34][35][36]48 Parents of children with autism need to be informed and trained so that they can become competent caregivers. Additionally, it is important to provide suitable counseling to families of children with autism to address their own feelings of grief and helplessness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A majority of the studies found that parents and families of children with autism have to go through a lot of difficulties to provide rehabilitation to their children. 17,26,[30][31][32][34][35][36]48 Parents of children with autism need to be informed and trained so that they can become competent caregivers. Additionally, it is important to provide suitable counseling to families of children with autism to address their own feelings of grief and helplessness.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, he expressed greater dissatisfaction on the satisfaction with life scale compared to the mother of the male adolescent with ASD. 32…”
Section: Challenges Faced By Parents and Family Of Child With Autismmentioning
confidence: 99%
See 2 more Smart Citations